Thermal elastohydrodynamic lubrication of heavily loaded line contacts-an efficient inlet zone analysis - Ghosh M.K.; Pandey R.K. (My University, 2025)
An inlet zone analysis of TEHD lubrication of heavily loaded line contacts has been done using a computationally efficient and accurate numerical method based on Lobatto quadrature developed by Elrod and Brewe (1986). The results under extremely heavy conditions of dimensionless load W = 5.2 * 10-4 (pH = 2.0 GPa) and dimensionless rolling velocity U = 2.0*10-10 (50 m/s) are presented. Significant reduction in thermal reduction factor (film thickness) at high rolling speeds relative to isothermal conditions have been observed. The results of the present work have been compared with the results of Wilson and Sheu (1983) and Km and Lee (1994). A correction formula of the thermal reduction factor for the minimum film thickness has been derived for a range of thermal loading parameters, loads, and slip ratios. © 1998 by ASME.